Immune Monitoring of Regulatory CD4 T Cells in Heart Recipients Using One-Single Dose Versus Two-Dose Basiliximab Induction. (July 2018) - Garcia, Sandra; Carbone, Javier; Sousa, Iago; Zatarain, Eduardo; Gallego, Antonio; Calahorra, Leticia; Sarmiento, Elizabeth
Abstract : Background: The use of induction immunosuppressive therapies in heart transplantation (HT) is still controversial. Delay in the initiation and reduced calcineurin inhibitor dose, due to renal failure and other settings are used as potential indications to induction use in some centers. On the other hand minimization of doses of monoclonal antibodies for induction therapy is indicated in some clinical settings such as high infection risk. Immunemonitoring of lymphocyte subsets after induction therapy might provide useful information. Methods: In a retrospective single center analysis of data prospectively collected, a comparative analysis of the kinetics of lymphocyte subsets was performed in patients using the recommended two doses [2D] of anti-IL2R-alpha monoclonal antibodies (Basiliximab, 20 mg, n=18) versus a single dose (1D, n=32). This was a non interventional study, single dose was indicated in specific clinical settings. We analysed the kinetics of regulatory CD4 T cells during the first 6 months after transplantation. Assessment points were pre-HT, day [d] 7, d15, d30, d60, d90 and d180. Maintenance immunosuppression included steroids, tacrolimus and mycophenolate mofetil in a similar way in both groups. Percentages and total counts of lymphocyte subsets were studied by flow-cytometry. Results: Baseline (pre-HT) percentages were similar in both groups (5.45±2.48 vs 5.36±3.31%, p=0.93). In 2D group, a decrease of CD4+CD25+CD127low regulatory cells was observed as compared with pre-transplant values between day 7 and 60; while in 1D patients there were not significant differences. Lower levels of regulatory CD4+ cells were observed up to d30 in 2D patients as compared with 1D patients: d7 2.52±2.62 vs 4.76±3.90%, p=0.046; d14 2.75±2.55 vs 5.08±5.17%, p=0.074 and d30 2.96±2.69 vs 5.61±3.78%, p=0.014. During the 6 months follow up there was no significant difference in the prevalence of acute cellular rejection in both groups. Conclusion: In a 6 month post transplant immunemonitoring follow-up study of a single cohort, one-dose of Basiliximab maintained higher levels of regulatory cells compared to a conventional 2-dose regimen. Since CD4 regulatory cells are considered to have an important role against allograft rejection, this information should be taken into account. The potential role of this cellular immune monitoring to assist in clinical decision making should be further explored in future studies. Fondo de Investigación Sanitaria. Project FIS 1501472. With participation of FEDER funds. A way of making Europe.